Distinct Hepatitis B and HIV co‐infected populations in Canada. Issue 3 (2nd January 2021) - Cooper, Curtis; Driedger, Matt; Wong, David; Haylock‐Jacobs, Sarah; Aziz Shaheen, Abdel; Osiowy, Carla; Fung, Scott; Doucette, Karen; Wong, Alexander; Barrett, Lisa; Conway, Brian; Ramji, Alnoor; et al.
Abstract: Due to shared modes of exposure, HIV‐HBV co‐infection is common worldwide. Increased knowledge of the demographic and clinical characteristics of the co‐infected population will allow us to optimize our approach to management of both infections in clinical practice. The Canadian Hepatitis B Network Cohort was utilized to conduct a cross‐sectional evaluation of the demographic, biochemical, fibrotic and treatment characteristics of HIV‐HBV patients and a comparator HBV group. From a total of 5996 HBV‐infected patients, 335 HIV‐HBV patients were identified. HIV‐HBV patients were characterized by older median age, higher male and lower Asian proportion, more advanced fibrosis and higher anti‐HBV therapy use (91% vs. 30%) than the HBV‐positive / HIV seronegative comparator group. A history of reported high‐risk exposure activities (drug use, high‐risk sexual contact) was more common in HIV‐HBV patients. HIV‐HBV patients with reported high‐risk exposure activities had higher male proportion, more Caucasian ethnicity and higher prevalence of cirrhosis than HIV‐HBV patients born in an endemic country. In the main cohort, age ≥60 years, male sex, elevated ALT, the presence of comorbidity and HCV seropositivity were independent predictors of significant fibrosis. HIV seropositivity was not an independent predictor of advanced fibrosis (adj OR 0.75 [95%CI: 0.34–1.67]). In conclusion, Canadian co‐infected patients differed considerably from those with mono‐infection. Furthermore, HIV‐HBV‐infected patients who report high‐risk behaviours and those born in endemic countries represent two distinct subpopulations, which should be considered when engaging these patients in care.